Direct synthesis of well-ordered and unusually reactive FeSBA-15 mesoporous molecular sieves - Vinu, A.; Sawant, D. P.; Ariga, Katsuhiko; Hossain, K. Z.; Halligudi, Shivappa B.; Hartmann, Martin; Nomura, M. (Chemistry of Materials, 2005)
Large-pore hexagonal SBA-15 molecular sieves partially substituted with iron(III) have been synthesized for the first time in highly acidic media. The degree of iron(III) incorporation into SBA-15 can easily be controlled by a simple adjustment of the molar ratio of water and hydrochloric acid. All the materials have been characterized by XRD, N-2 adsorption, UV-Vis DRS, ESR, and XANES spectroscopy. The characterization of the FeSBA-15 materials by UV-Vis DRS, ESR, and XANES spectroscopies suggests that the iron atoms are highly dispersed and mostly occupy isolated tetrahedral sites. XANES studies revealed that the proportion of tetrahedrally coordinated Fe atoms decreases with decreasing n(Si)/n(Fc) ratios. Benzylation of benzene (or substituted benzenes) using benzyl chloride as the alkylating agent over FeSBA-15 with different n(Si)/n(Fe) ratios was investigated as was the same reaction using AISBA-15 as catalyst. The influence of parameters such as reaction temperature, reactant feed ratio, and the presence of electron-donating substituents on the activity and selectivity of AISBA-15 was studied. Under optimized reaction conditions, the FeSBA-15 catalyst showed a superior catalytic performance in the benzylation of benzene and other aromatics using benzyl chloride, with a clean conversion of benzyl chloride to the monoalkylated product (100% selectivity) with a very high rate constant when compared to other mesoporous materials such as AISBA-15 and FeHMS. Interestingly, use of FeSBA-15(21) resulted in quantitative conversion of benzyl chloride with a high rate constant of 2420.5 x 10(-4) min(-1) under the optimized reaction conditions.